PENGARUH INDEPENDENSI AUDITOR DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT - Richard Andrew; Lusy Lusy; Winda Septina (Jurnal Akuntansi dan Pajak, 2023)
An auditor is required to always maintain independence in producing audit quality. The covid 19 pandemic makes the time budget pressure of an auditor unstable, auditors are always required to produce audit reports within the set time limits. After this pandemic, whether an auditor is still able to maintain the quality of the audit produced is a big question today. The object of this study are all auditors registered in KAP Surabaya. Surabaya location selection because Surabaya is the second largest city in Indonesia and one of the largest industries that contribute to the economy in Indonesia, after Jakarta. The purpose of this study was to examine the effect of auditor independence, and time budget pressure on the quality of audits produced by an auditor. The specific purpose of this study is to see the level of independence and time budget of an auditor whether it is maintained after the covid 19 pandemic. The urgency of this study is that if auditors have different levels of independence and sustainability post-pandemic, especially coupled with audit digitization, the special specifications in this study, focus more on the theme of sustainable auditor research in terms of independence and time budget pressure. Keywords : Independence, time Budget Pressure, Audit Quality, Auditor JEL Clasification : Audit